PERBANDINGAN KARAKTERISTIK POLA PENYEDIA INFRASTRUKTUR PERMUKIMAN PADAT TINGGI DAN RENDAH KASUS DI DANUKUSUMAN DAN MOJOSONGO KOTA SURAKARTA - Wahyu Putri N.I.S; Kuswanto Nurhadi; Isti Andini (Universitas Sebelas Maret Surakarta, 2015)
Surakarta has five subdistrict. Subdistrict with the highest density is Serengan and subdistrict with the lowest density is Jebres. In Serengan, Danukusuman is the crowded, whereas in Jebres, Mojosongo is the lowest density. Density differences problem can result in differences in the activity of the people who live. Then can affect the differences in infrastructure needs and patterns of settlement there is the provision of infrastructure (actor variations and details of cooperation). So, this study done to know the characteristic comparison of high and low density settlements infrastructure provision pattern in Danukusuman and Mojosongo. To gain it, carried out was used a comparative analysis of settlement characteristics both in terms of physical, economic and socio-cultural. further analysis is to compare the characteristics of the infrastructure available with the applicable standards (SNI). then, final analysis is to determine and compare the pattern of provision of infrastructure and settlements in Danukusuman and Mojosongo. the results of the analysis is known that that there was no significant difference between high dense settlements (Danukusuman) and low dense settlements (Mojosongo) both from the aspect of the character of the location, infrastructure preparation and provision pattern. Only difference is quite prominent at the level of the economy and the provision of communal wastewater infrastructure that influenced by the density of settlement, while the difference in the provision of clean water is more influenced by the character of the location / the physical settlement. Keywords: high and low density, pattern of provision of infrastructure settlement infrastructure,